Effect of manufacturing defect on mechanical performance of plain weave carbon/epoxy composite based on 3D geometrical reconstruction. (1st September 2018) - Wang, Panding; Lei, Hongshuai; Zhu, Xiaolei; Chen, Haosen; Wang, Changxian; Fang, Daining
Abstract: The investigation on the effect of manufacturing defect on the mechanical performance of composite is essential for the design and application in practice. In this study, the plain weave carbon fiber reinforced polymer (CFRP) laminates are fabricated by the autoclave process and vacuum bag process (VBP), respectively. Uniaxial tensile testes are conducted with a digital image correlation (DIC) system to obtain the macroscopic mechanical performance and local strain distribution. The internal microdefects of composite laminates are captured by micron-resolution computed tomography (μCT) detection technique, including the size and distribution of void, total volume fraction and geometrical parameters of yarns. Based on the Texgen software and Monte-Carlo algorithm, virtual samples with various void contents are constructed to evaluate the impact of defect using finite element solver ABAQUS/Standard. To substantiate this work, we present a comparative study considering both autoclave and VBP. The effect of void defect on the mechanical performances of CFRP laminate is analyzed through finite element method (FEM). The results reveal that the effect of void defect on the surface strain distribution of laminate is significant, especially the value of maximum strain, which will increase obviously with the void defect content. In addition, the overall stiffness predicted by numerical simulation, taking the effect of void defect into account, is lower than that of theoretical.